Built-In Content sebagai Pesan Komunikasi Pemasaran pada Program Rating 5 GTV - Amanu, Zhevio Aufa; Priatna, Wahyu Budi (Universitas Islam Balitar, 2025)
This study analyzes the effectiveness of built-in content strategies as a form of marketing communication in the